Binocular treatment for amblyopic children: a review - Bokhary, Kholoud Ahmad; Alsabih, Razan Ibrahim; Gamal Abdelrahman El-Hiti (Journal of the Pakistan Medical Association, 2023)
The narrative review was planned to investigate the efficiency of binocular treatment for amblyopic children, and to compare it with the standard methods. Literature search was conducted for articles in English language available on PubMed, Cochrane Library, Embase, Medline and PsycInfo databases as well as through bibliographies of peer-reviewed studies. Studies in the field of binocular treatment for amblyopia were included. Visual outcomes considered were visual acuity, types of amblyopia and stereoacuity. Studies on deprivation amblyopia, animal studies, literature review of amblyopia treatment, case reports, and trials targeting participants in whom previous amblyopia treatment had failed were excluded. Of the 40 studies found, 21(52.5%) met the inclusion criteria. Visual acuity and binocular function improved with binocular treatment for treating amblyopia in children by decreasing suppression depth extent and increasing stereopsis. —Continue